Strategi Politik PDI Perjuangan Dalam Memenangkan Figur Perempuan Pada Pemilihan Kepala Daerah Buru Selatan 2020 - Sampulawa, Selmin; Tuanaya, Wahab; Muhtar, Muhtar (Prodi Ilmu Pemerintahan, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Pattimura, 2023)
This research is a qualitative description with the aim of describing the PDI Perjuangan Political Strategy in Winning Female Figures in the 2020 South Buru Pilkada. Data collection was carried out using secondary data and primary data. The results of this study indicate that during the election momentum, of course, people tend to see the figure or character of the regional head candidates, so this is also related to political parties as a forum for delivering a candidate to succeed or not succeed in the next regional election. PDI-Perjuangan as a party that carries a female figure in the 2020 regional elections, of course, carries strength from the PAC-PAC to the branches to work intensively to win Mrs. Safitri as the first female regent in Maluku. From the aspect of electability and popularity like this, a survey has been carried out so that we can find out how interested a person is in voting or a candidate who is well known among the southern Buri community